Ajuste de algunos modelos contagiosos en conteos de diatraea saccharalis mediante el método de VTM - Claros Reyna, José Brian (2013)
This paper proposes the evaluation of contagion models (Neyman type A negative binomial and Poisson) to evaluate by the sequential sampling protocol effectiveness of aggregate models, the spatial distributions for distributions in populations aggregative insects - pest may be the result of physical and biological factors. Physical factors create a heterogeneous environment and so all areas are equally attractive or not receptive to insects. In this paper we reaffirm that the aggregate distribution Neyman type A (Poisson - Poisson) is the most efficient for spatial arrangement in which we find (for similarity of creation and order it), considering how distributed of insects is evolving and changing according to a parameter not only aggregation but many more which do not contemplate in this work